Effect of adding marjoram leaf extract to drinking water for broiler chickens on certain production traits (Indian Journal of Animal Production and Management, 2025)
This experiment was conducted at the Department of Animal Production,  Faculty of Agriculture, University of Karbala, between November 10,  2023, and December 22, 2023, to study the effect of adding marjoram  water extract to drinking water on the production performance of broiler  chickens. The study aimed to determine the effect of adding different  levels of Origanum majorana powder extract to feed on the productive  performance of broiler chickens and some blood components. One  hundred and fifty 7-day-old Ros 308 chicks were used, and the experiment  lasted 35 days. The birds were randomly distributed into four treatments,  with 60 chicks per treatment. The chicks were fed starter and finisher feeds  with crude protein levels of 23% and 21.5% and energy levels of 3027 and  3195.3 kcal/kg of feed, respectively. An aqueous extract of marjoram was  added at the following rates (20 ml/l rinking water) for the second group. 30 ml/l drinking water) for  the third group. (40 ml/l drinking water) for the fourth group. The first group (control) was given normal drinking water without any  additives The results of the experiment indicated significant increase (p
Keywords: genetics; medicine; chicken; broiler; immunity